Pengaruh Efektivitas Penerimaan Pajak Dan Retribusi Daerah Terhadap Pendapatan Asli Daerah Kota - Dessy Wulandari; Nurlaila Nurlaila (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
This study aims to determine the effect of the effectiveness of local tax revenues and levies on local revenue in the city of Medan in 2016-2018. The independent variables used in this study are the effectiveness of local tax revenues and the effectiveness of local retribution receipts, while the dependent variable is local revenue. The type of research used is associative. The population used in this study is the regional government budget realization report of Medan City. The number of samples was 36 months during the 2016-2018 period, with the sampling technique using the time series method. The type of data used in this research is quantitative data. The data source used in this research is secondary data. The results show that partially the effectiveness of regional tax revenues (X1) has a positive effect on regional original income, the effectiveness of local retribution receipts (X2) has a positive effect on regional original income. The value of is 0.991, which means that 99.1% of local revenue is influenced by the effectiveness of local tax revenue and the effectiveness of receiving local user fees, while 0.09% is explained by other variables which are not tested in this study.